SESSILE PELVIC OSTEOCHONDROMA: A RARE CASE THAT REQUIRED ABDOMINAL WALL RECONSTRUCTION AFTER EXCISION - Zamir, Mehroze; Ahmed, Nasir; Iqbal, Faizan; Kamal, Syed Wajahat (Journal of Ayub Medical College Abbottabad, 2023)
Osteochondroma are the most common benign tumours of the bone presenting in the young age group. Commonly found at the metaphysis of the long bones and mostly pedunculated; atypical locations and sessile appearances have also been described in literature. Due to the risk of conversion to malignant chondrosarcoma, the recommended treatment of these lesions is complete excision. We encountered a similar sessile growth in the pelvic region of a 21-year-old male with complaints of pain and swelling. After thorough investigation, excisional biopsy was performed and abdominal wall repair was reinforced with a polypropylene mesh. Careful evaluation, adequate investigations and meticulous surgical treatment can avoid potential problems in managing these tumours